A filamin A splice mutation resulting in a syndrome of facial dysmorphism, periventricular nodular heterotopia, and severe constipation reminiscent of cerebro-fronto-facial syndrome. Issue 6 (18th November 2005) - Hehr, U; Hehr, A; Uyanik, G; Phelan, E; Winkler, J; Reardon, W
Abstract : Background: Mutations of the filamin A locus ( FLNA ) on Xq28 have been established in girls with periventricular nodular heterotopia and in patients with otopalatodigital and overlapping phenotypes, the pathogenesis of these phenotypes being thought to be quite distinct. To date only six male cases of periventricular nodular heterotopia (PVNH) have been reported and these almost invariably associated with severe neurological signs. Methods and Results: We report a new phenotype of male PVNH, with relatively normal development, no epilepsy or other neurological abnormality, severe constipation, and facial dysmorphism and without a discernible skeletal phenotype. This phenotype is associated with a splice site mutation in FLNA c.1923C>T, resulting in the generation of both normal and aberrant mRNA. Conclusions: We postulate that the patient retains enough FLNA function to avoid the usual lethality associated with loss of function mutations in males and suggest that the severe constipation may be a clue to the molecular aetiology of other X linked conditions associated with severe constipation.